2007
DOI: 10.1097/mca.0b013e328011c084
|View full text |Cite
|
Sign up to set email alerts
|

Systemic application of anti-ICAM-1 monoclonal antibodies to prevent restenosis in rabbits: an anti-inflammatory strategy

Abstract: Administration of anti-ICAM-1 mAb following either balloon angioplasty or stent implantation results in a suppression of bFGF in the early phase of restenosis, whereas TGF-beta significantly increases from 7 to 14 days after stent implantation independent of anti-ICAM-1 mAb application. Therefore we conclude that anti-inflammatory strategies are able to interfere with growth factor expression after vascular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Therefore, the antibody could reduce the adhesion force between ICAM-1 and CD11b (Figure 4). This result not only verified that our method could be used to study the binding force change, but also implied the potential of ICAM-1 monoclonal antibody drugs in the antiinflammatory therapeutic areas [39,40].…”
Section: The Effect Of Icam-1 Monoclonal Antibodies On the Binding Besupporting
confidence: 80%
“…Therefore, the antibody could reduce the adhesion force between ICAM-1 and CD11b (Figure 4). This result not only verified that our method could be used to study the binding force change, but also implied the potential of ICAM-1 monoclonal antibody drugs in the antiinflammatory therapeutic areas [39,40].…”
Section: The Effect Of Icam-1 Monoclonal Antibodies On the Binding Besupporting
confidence: 80%
“…Patients with the C/C genotype were more frequently diagnosed with an aggressive form of this disease compared to G allele carriers [ 19 ]. Experimental studies have demonstrated that bFGF levels increase in the first hours after balloon angioplasty or stent implantation, which may be related to intensified inflammatory response [ 54 ], whereas SMC proliferation after arterial wall injury is inhibited by antibodies directed against bFGF [ 55 ]. However, in dogs undergoing iliac artery angioplasty, bFGF infusion restored endothelium-dependent and -independent relaxation of the arterial wall and reduced LLL [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in expression or over‐expression of adhesion molecules were observed in inflammatory and allergic processes as well as in malignant tumors of humans (148). Attempts to block the action of these molecules as a novel therapeutic approach were undertaken using in vitro models and in experimental animals as well as in humans (reviewed in 213,214). These studies used antibodies and antisense oligonucleotides against human adhesion molecules (213–222).…”
Section: Attempts At Therapeutic Application Of Antibodies To Adhesiomentioning
confidence: 99%